High-temperature alloy oxidation resistance high-throughput testing method and testing sample thereof

CN122983117APending Publication Date: 2026-10-27UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206120.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,在实际服役中,由于氧化膜易开裂、剥落或生长速率失控,导致基体失去保护而发生灾难性氧化,最终引发构件失效

Benefits of technology

(1)高通量制备效率高:本发明突破了传统熔炼-锻造-加工的漫长周期,利用SLM技术原位合成成分梯度材料,实现了单次打印即可获得涵盖宽成分范围(Cr: 0-22 at.%,Al: 1-5 at.%)的合金试样,大幅缩短了合金研发周期。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122983117A_ABST
    Figure CN122983117A_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature alloy oxidation resistance high-throughput testing method and a testing sample thereof, and belongs to the technical field of nickel-based high-temperature alloys. The method is based on Ni-based high-temperature alloys with an Al mass fraction of 0-5%, and ten powders are prepared, including a high-chromium group with a Cr content of 22% and a low-chromium group with a Cr content of 0%. A two-channel powder feeding system of a selective laser melting technology is used to control the powder feeding ratio of the two sides, in-situ synthesize a binary gradient alloy sample with continuously changing Cr and Al contents in a single printing process, and obtain a wide composition coverage gradient material with a Cr content of 0-22 wt.% and an Al content of 0-5 wt.%. The gradient sample prepared by the method has a dense structure, uniform composition transition and good interface metallurgical bonding, and can be directly used for high-temperature isothermal oxidation testing. In combination with micro-area characterization means, the oxidation film characteristics under different Cr and Al ratios can be quickly obtained, and the synergistic action law of different alloy elements on the oxidation resistance can be efficiently revealed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nickel-based superalloy technology, and particularly relates to a high-throughput testing method for the oxidation resistance of superalloys and the test specimen thereof. Background Technology

[0002] Nickel-based superalloys, due to their excellent high-temperature strength, creep resistance, and toughness, have become core materials for hot-end components in aero-engines, gas turbines, and chemical equipment. With the development of modern industry, these equipment are moving towards higher parameters (temperature, pressure), which places more stringent requirements on the long-term structural stability and environmental damage resistance of alloys in complex service environments.

[0003] In high-temperature steam environments, nickel-based superalloys face severe challenges from high-temperature steam oxidation. Studies have shown that the oxidation resistance of alloys mainly depends on the integrity of the protective oxide film formed on the surface. Cr and Al are key alloying elements in oxide film formation: Cr tends to form Cr₂O₃, and Al tends to form Al₂O₃. An ideal oxide film should be dense, continuous, grow slowly, and be firmly bonded to the substrate to act as an effective barrier against oxygen diffusion. However, in actual service, the oxide film is prone to cracking, peeling, or uncontrolled growth, leading to catastrophic oxidation of the substrate due to lack of protection, ultimately causing component failure.

[0004] Therefore, it is particularly important to break through the long cycle of traditional smelting-forging-processing and develop efficient testing methods for the oxidation resistance of high-temperature alloys to significantly shorten the alloy research and development cycle. Summary of the Invention

[0005] In view of this, the present invention discloses a high-throughput testing method for the oxidation resistance of high-temperature alloys and the test specimen thereof.

[0006] The present invention adopts the following technical solution: A high-throughput testing method for the oxidation resistance of high-temperature alloys, wherein the alloys comprise Al and Cr, the method comprising the following steps: S1. A Ni-based superalloy powder with a gradient of Al mass fraction (wt.%) is used as the base system; for each gradient of the Ni-based superalloy powder, a high-chromium nickel-based alloy powder is prepared with a mass fraction of 22 wt.% Cr and a mass fraction of 0 wt.% Cr. A low-chromium nickel-based alloy powder is obtained by preparing a powder with a mass fraction of 22 wt.% Cr and a powder with a mass fraction of 0 wt.% Cr. S2. Using the dual-channel powder feeding system of the selective laser melting equipment, the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder with the same Al mass fraction are respectively loaded into the right and left channels of the feeding mold; S3. Control the powder feeding ratio of the dual-channel powder feeding system, print and spread layer by layer on the printing platform and melt deposit to obtain a molded sample, so that the molded sample forms a continuous gradient distribution of Cr mass fraction from 0 wt.% to 22 wt.% in the length direction; S4. Replace the powder group with different Al mass fractions and repeat the above printing steps to obtain a series of nickel-based superalloy samples with different Al reference contents and Cr contents that vary in gradient. Test the high-temperature oxidation resistance of the nickel-based superalloy samples and screen out the optimal composition range.

[0007] Further, the Ni-based superalloy powder with a gradient Al mass fraction mentioned in step S1 is of five types, and the Al mass fraction (wt.%) in the five types of Ni-based superalloy powder are 1%, 2%, 3%, 4% and 5%, respectively. The five types of Ni-based superalloy powder are respectively prepared by formulating 22 wt.% Cr and 0 wt.% Cr to obtain ten powder raw materials.

[0008] Furthermore, the oxygen content in both the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder described in step S1 is controlled to be below 0.02 wt.%.

[0009] Furthermore, the particle size of the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder in step S2 is independently 15–53 μm.

[0010] Further, the melting process parameters in step S3 are: laser power 350-480 W, laser scanning speed 650-800 mm / s, scanning interval 100 μm, and powder layer thickness 20-50 μm.

[0011] Furthermore, the gradient distribution described in step S3 exhibits a linear change, and this change satisfies the following relationship: C Cr =kx; where C Cr The percentage content (wt.%) of the high-chromium nickel-based alloy powder; x is the coordinate along the length of the molded sample; k is the gradient coefficient; as x changes from 0 to the total length L of the molded sample, C Cr It increased continuously from 0 wt.% to 22 wt.%.

[0012] Furthermore, the high-temperature oxidation resistance test described in S4 includes: after standard pretreatment, the obtained alloy sample is placed in a high-temperature oxidation furnace and kept at 900°C in static air for 1000 hours. After cooling with the furnace, oxidation samples with different composition ratios are obtained and the oxide film is characterized.

[0013] A high-throughput nickel-based superalloy sample, the alloy sample being prepared using the method described above.

[0014] Furthermore, the alloy sample is configured with a continuous gradient distribution of Cr elements along its length and a discontinuous grouping distribution of Al elements along its width or height.

[0015] An application of the above method in high-throughput screening of antioxidant components in nickel-based superalloys.

[0016] The beneficial effects of this invention are as follows: (1) High throughput and high efficiency: This invention breaks through the long cycle of traditional smelting-forging-processing. It uses SLM technology to synthesize composition gradient materials in situ, and realizes that alloy samples covering a wide composition range (Cr: 0-22 at.%, Al: 1-5 at.%) can be obtained in a single printing, which greatly shortens the alloy research and development cycle.

[0017] (2) Precise composition control: By precisely controlling the powder feeding ratio of the dual channels, the continuous or discontinuous (stepped) gradient distribution of Cr and Al elements at the microscale is realized, eliminating the interference of the interface reaction layer in the traditional diffusion couple method, and the composition has strong traceability. (3) Revealing the interaction of multiple components: This method can systematically study the influence of Cr and Al binary components on the growth kinetics and phase stability of high-temperature oxide films under different ratios, providing reliable data support for optimizing the failure-resistant design of nickel-based high-temperature alloys.

[0018] (4) Good process compatibility: The method is applicable to a variety of nickel-based high-temperature alloy systems. The prepared gradient samples can be directly used for oxidation testing or mechanical property testing without subsequent cutting, which reduces the experimental cost. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic diagram of the process for a high-throughput testing method for the oxidation resistance of high-temperature alloys according to the present invention. Figure 2 This is a schematic diagram of the gradient printing method for nickel-based superalloys with different chromium and aluminum contents in the present invention. Detailed Implementation

[0021] To better understand the technical solution of the present invention, the embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0022] Example 1

[0023] A high-throughput testing method for the oxidation resistance of high-temperature alloys, wherein the alloys comprise Al and Cr, such as Figure 1 As shown, Figure 1 This is a schematic diagram of a high-throughput testing method for the oxidation resistance of high-temperature alloys according to the present invention. The method includes the following steps: S1. A Ni-based superalloy powder with a gradient of Al mass fraction (wt.%) is used as the base system; for each gradient of the Ni-based superalloy powder, a high-chromium nickel-based alloy powder is prepared with a mass fraction of 22 wt.% Cr and a mass fraction of 0 wt.% Cr. A low-chromium nickel-based alloy powder is obtained by preparing a powder with a mass fraction of 22 wt.% Cr and a powder with a mass fraction of 0 wt.% Cr. S2. Utilizing a dual-channel powder feeding system of selective laser melting equipment, such as Figure 2 As shown, the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder with the same Al mass fraction are respectively loaded into the right and left channels of the feeding mold to achieve batch processing, control of single composition, and horizontal printing of Cr element gradient and vertical printing of Al gradient. S3. Control the powder feeding ratio of the dual-channel powder feeding system, print and spread layer by layer on the printing platform and melt deposit to obtain a molded sample, so that the molded sample forms a continuous gradient distribution of Cr mass fraction from 0 wt.% to 22 wt.% in the length direction; S4. Replace the powder group with different Al mass fractions and repeat the above printing steps to obtain a series of nickel-based superalloy samples with different Al reference contents and Cr contents that vary in gradient. Test the high-temperature oxidation resistance of the nickel-based superalloy samples and screen out the optimal composition range.

[0024] Further, in step S1, five types of Ni-based superalloy powders with gradient Al mass fractions are used, and the Al mass fractions (wt.%) in the five types of Ni-based superalloy powders are 1%, 2%, 3%, 4%, and 5%, respectively. Ten powder raw materials are obtained by preparing 22 wt.% Cr and 0 wt.% Cr from the five types of Ni-based superalloy powders. In practical application, it was found that when the Al mass fractions (wt.%) in the Ni-based superalloy powders are 1%, 2%, 3%, 4%, and 5%, the ten powder raw materials obtained by preparing them with 22 wt.% Cr and 0 wt.% Cr exhibit the best practical application effect. This ratio, when the powder feeding ratio of the dual-channel powder feeding system is controlled, allows for layer-by-layer printing on the printing platform to form a continuously gradient distribution of Cr mass fraction from 0 wt.% to 22 wt.%, resulting in more uniform control of the continuous gradient distribution and effectively improving the testing results of this invention.

[0025] Furthermore, in the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder mentioned in step S1, the types and mass fractions of other alloying elements, except for Cr, are consistent, and the oxygen content is controlled below 0.02 wt.%.

[0026] Furthermore, the particle size of the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder in step S2 is independently 15–53 μm.

[0027] Furthermore, the selective laser melting (melting) process parameters in step S3 are: laser power 350-480 W, laser scanning speed 650-800 mm / s, scanning interval 100 μm, and powder layer thickness 20-50 μm.

[0028] Furthermore, the gradient distribution described in step S3 exhibits a linear change, and this change satisfies the following relationship: C Cr =kx; where C Cr The percentage content (wt.%) of the high-chromium nickel-based alloy powder; x is the coordinate along the length of the molded sample; k is the gradient coefficient; as x changes from 0 to the total length L of the molded sample, C Cr It increased continuously from 0 wt.% to 22 wt.%.

[0029] Furthermore, the high-temperature oxidation resistance test described in S4 includes: after standard pretreatment, the obtained alloy sample is placed in a high-temperature oxidation furnace and kept at 900°C in static air for 1000 hours. After cooling with the furnace, oxidation samples with different composition ratios are obtained and the oxide film is characterized.

[0030] A high-throughput nickel-based superalloy sample, the alloy sample being prepared using the method described above.

[0031] Furthermore, the alloy sample is configured with a continuous gradient distribution of Cr elements along its length and a discontinuous grouping distribution of Al elements along its width or height.

[0032] An application of the above method in high-throughput screening of antioxidant components in nickel-based superalloys.

[0033] Example 2

[0034] A method for studying the effects of chromium and aluminum content on the oxidation resistance of nickel-based superalloys includes the following steps: Adjust the height of the printer's feed bar and printing bar so that the scraper scrapes a thin layer of powder onto the printing bar. Then lower the feed bar by 3cm.

[0035] S1. Using a dual-channel model, place high-chromium nickel-based high-temperature alloy powder with an aluminum content of 1% and a particle size of 50μm into the right channel of the mold, and low-chromium nickel-based high-temperature alloy powder with an aluminum content of 1% and a particle size of 50μm into the left channel of the mold. Remove the mold and keep the powder and powder steel separately. S2. At this time, the program is set to make the scraper scrape a layer of material and send it into the printing steel, and send the high chromium nickel-based alloy powder and the low chromium nickel-based alloy powder to the printing table. S3. At this time, according to the set program, the laser power during the laser melting process is 350-480W, the printing speed is 0.1cm / s, the scanning speed is 650mm / s, and the scanning interval is 100μm. The steel material is continuously discharged under the action of the scraper, and the high chromium nickel-based alloy powder and low chromium nickel-based alloy powder are sent to the printing table to obtain a layer-by-layer stacked mixed printing powder. S4. After printing a nickel-based superalloy with an aluminum content of 1% and a chromium gradient, replace the powder and repeat step S1. Replace the powder with a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 5% by mass. Repeat this process for nickel-based superalloys with aluminum content of 3%, 4%, and 5% by mass. S5. Five rectangular powder matrices (110 mm × 10 mm × 10 mm) were printed and placed in a QIH-9 laboratory-grade hot isostatic pressing (HIP) system for 6 hours at 1200℃ and 150 MPa. Subsequently, a solution treatment was performed at 1200℃ for 24 hours in an argon atmosphere to eliminate local component segregation. Internal defects in the powder matrix were characterized using X-ray micro-computed tomography (Micro-CT) on a YXLON FF35 laboratory system. Three-dimensional (0.5 mm × 0.5 mm × 2 mm) local component analysis was performed on low, medium, and high chromium concentration regions along the composite alloy gradient. No cracks were found in the powder matrix, and the porosity was 0.13 ± 0.05%. The powder matrix samples were then mechanically ground and polished according to standard metallographic preparation methods. The treated powder matrix was placed in an oxidation furnace at 900℃ for 1000 hours in an air-filled environment to obtain oxidation samples with different alloy element ratios.

[0036] The oxidized sample surfaces were subjected to gold sputtering and nickel plating, followed by standard metallographic preparation methods. The cross-sectional microstructure of the oxide film was observed using a Zeiss Supra 55 scanning electron microscope (SEM) in backscattered electron mode. It was found that the overall oxide layer thickness was lower in the five oxidized samples with an aluminum atomic content of 4%. Furthermore, within the aluminum strips of this composition, the oxide layer thickness increased continuously with increasing Cr content. However, after the Cr content reached 13%, the oxide layer thickness exhibited a sudden change, becoming several times thinner than the oxide layer thickness of the first 13% of the composition, indicating that this alloy composition has good oxidation resistance.

[0037] Ultimately, it was found that the chromium mass ratio of the oxidized sample cross-section was about 13%, the aluminum mass ratio was about 4%, the oxide layer thickness was the smallest, and the oxide layer thickness increased at a smaller rate over time. Furthermore, analysis showed that the outer oxide layer was Cr2O3 and the inner oxide layer was Al2O3, at which point the oxidation resistance was the best.

[0038] Example 3

[0039] Adjust the height of the printer's feed bar and printing bar so that the scraper scrapes a thin layer of powder onto the printing bar. Then lower the feed bar by 4cm.

[0040] S1. Using a dual-channel model, place high-chromium nickel-based high-temperature alloy powder with an aluminum content of 1% and a particle size of 70μm into the right channel of the mold, and low-chromium nickel-based high-temperature alloy powder with an aluminum content of 1% and a particle size of 70μm into the left channel of the mold. Remove the mold and keep the powder and powder steel separately. S2. At this time, the program is set to make the scraper scrape a layer of material and send it into the printing steel, and send the high chromium nickel-based alloy powder and the low chromium nickel-based alloy powder to the printing table. S3. At this time, according to the set program, the laser power during the laser melting process is 80W, the printing speed is 2cm / s, the scanning speed is 800mm / s, and the scanning interval is 100μm. The steel material is continuously discharged under the action of the scraper, and the high chromium nickel-based alloy powder and low chromium nickel-based alloy powder are sent to the printing table to obtain the mixed printing powder stacked layer by layer. S4. After printing a nickel-based superalloy with an aluminum content of 1% and a chromium gradient, replace the powder and repeat step S1. Replace the powder with a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 2% by mass and a nickel-based superalloy powder with an aluminum content of 5% by mass. Repeat this process for nickel-based superalloys with aluminum content of 3%, 4%, and 5% by mass. S5. Six rectangular powder substrate samples (110 mm × 10 mm × 10 mm) were printed and placed in a QIH-9 laboratory-grade hot isostatic pressing (HIP) system for 6 hours at 1200℃ and 150 MPa. Subsequently, a solution treatment was performed at 1200℃ for 24 hours in an argon atmosphere to eliminate local component segregation. Internal defects in the powder substrate were characterized using X-ray micro-computed tomography (Micro-CT) on a YXLON FF35 laboratory system. Three-dimensional (0.5 mm × 0.5 mm × 2 mm) local component analysis was performed on low, medium, and high chromium concentration regions along the composite alloy gradient. No cracks were found in the powder substrate, with porosities of 0.13 ± 0.05%. The powder substrate samples were then mechanically ground and polished according to standard metallographic preparation methods. The treated powder substrates were placed in an oxidation furnace at 900℃ for 1000 hours in an air-filled environment to obtain oxidation samples with different alloy element ratios.

[0041] The oxidized sample surfaces were subjected to gold sputtering and nickel plating, followed by standard metallographic preparation methods. The cross-sectional microstructure of the oxide film was observed using a Zeiss Supra 55 scanning electron microscope (SEM) in backscattered electron mode. It was found that the overall oxide layer thickness was lower in the five oxidized samples with an aluminum atomic content of 4%. Furthermore, within the aluminum strips with this composition, the oxide layer thickness increased continuously with increasing Cr content. However, after the Cr content reached 13%, the oxide layer thickness exhibited a sudden change, becoming several times thinner than the oxide layer thickness in the first 13% composition, indicating good oxidation resistance.

[0042] Ultimately, it was found that the chromium mass ratio of the oxidized sample cross-section was about 13%, the aluminum mass ratio was about 4%, the oxide layer thickness was the smallest, and the oxide layer thickness increased at a smaller rate over time. Furthermore, analysis showed that the outer oxide layer was Cr2O3 and the inner oxide layer was Al2O3, at which point the oxidation resistance was the best.

[0043] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A high-throughput testing method for the oxidation resistance of a high-temperature alloy, wherein the alloy comprises Al and Cr, characterized in that, The method includes the following steps: S1. A Ni-based superalloy powder with a gradient Al mass fraction is used as the base system; for each gradient of the Ni-based superalloy powder, a high-chromium nickel-based alloy powder with a mass fraction of 22% Cr and a mass fraction of 0% Cr are prepared respectively. A low-chromium nickel-based alloy powder is obtained by preparing a powder with a mass fraction of 22% Cr and a low-chromium nickel-based alloy powder with a mass fraction of 0% Cr. S2. Using the dual-channel powder feeding system of the selective laser melting equipment, the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder with the same Al mass fraction are respectively loaded into the right and left channels of the feeding mold; S3. Control the powder feeding ratio of the dual-channel powder feeding system, print and spread layer by layer on the printing platform and melt deposit to obtain a molded sample, so that the molded sample forms a continuous gradient distribution of Cr mass fraction from 0% to 22% in the length direction; S4. Replace the powder group with different Al mass fractions and repeat the above printing steps to obtain a series of nickel-based superalloy samples with different Al reference contents and Cr contents that vary in gradient. Test the high-temperature oxidation resistance of the nickel-based superalloy samples and screen out the optimal composition range.

2. The method according to claim 1, characterized in that, The Ni-based superalloy powders with gradient Al mass fractions mentioned in step S1 are of five types, with Al mass fractions of 1%, 2%, 3%, 4%, and 5% respectively. Ten powder raw materials are obtained by preparing powders with 22% Cr and 0% Cr mass fractions, respectively.

3. The method according to claim 2, characterized in that, In step S1, the oxygen content in both the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder is controlled to be below 0.02 wt.%.

4. The method according to claim 2, characterized in that, The particle size of the high-chromium nickel-based alloy powder and the low-chromium nickel-based alloy powder mentioned in step S2 is 15-53 μm.

5. The method according to claim 2, characterized in that, The melting process parameters in step S3 are: laser power 350-480 W, laser scanning speed 650-800 mm / s, scanning interval 100 μm, and powder layer thickness 20-50 μm.

6. The method according to claim 2, characterized in that, The gradient distribution described in step S3 exhibits a linear change, and this change satisfies the following relationship: C Cr =kx; where C Cr is the mass percentage content of the high-chromium nickel-based alloy powder; x is the coordinate along the length of the molded sample; k is the gradient coefficient; as x changes from 0 to the total length L of the molded sample, C Cr It increased continuously from 0% to 22%.

7. The method according to claim 2, characterized in that, The high-temperature oxidation resistance test described in S4 includes: after standard pretreatment, the obtained alloy sample is placed in a high-temperature oxidation furnace and kept at 900°C in static air for 1000 hours. After cooling with the furnace, oxidation samples with different composition ratios are obtained and the oxide film is characterized.

8. A high-throughput nickel-based superalloy test specimen, characterized in that, The test specimen was prepared using the method described in any one of claims 1-7.

9. The test specimen according to claim 8, characterized in that, The test sample is constructed with a continuous gradient distribution of Cr elements along its length and a discontinuous grouping distribution of Al elements along its width or height.

10. The application of the method as described in any one of claims 1-7 in high-throughput screening of antioxidant components in nickel-based superalloys.